The impact of belongingness and graphic-based emoticon usage motives on emoticon purchase intentions for MIM: an analysis of Korean KakaoTalk users - Jung, Bohee; Kim, Hanku; Lee, Seung Hwan (Shawn) (Online Information Review, 2022)
Purpose: Although graphic-based emoticons in mobile instant messenger (MIM) services became an important revenue source for their service provider, empirical research investigating factors influencing graphic-based emoticon purchase from the consumer's perspective is insufficient. The authors explore how user's achieved belongingness (acceptance or rejection) affects graphic based emoticon usage motivations and its purchase intentions. Design/methodology/approach: A structural model is used to examine the relationship among individual's overall achieved belongingness, motivation factors of graphic-based emoticon usage in MIM such as perceived usefulness, perceived enjoyment, perceived enjoyment for others, social norm and emoticon purchase intentions. The authors collected and analyzed survey data of 279 Korean KakaoTalk users. Findings: The analysis shows that perceived acceptance/inclusion positively impacts perceived usefulness, enjoyment and enjoyment of others in graphic-based emoticon usage. Meanwhile, perceived rejection/exclusion positively impacts perceived enjoyment and enjoyment of others but negatively influences perceived social norms. Moreover, social norms and perceived enjoyment directly affect graphic-based emoticon purchase intentions. The authors also find that perceived enjoyment of others and perceived social norms in a serial causal order mediate the relationship between perceived acceptance/inclusion (and rejection/exclusion) and emoticon purchase intentions. Research limitations/implications: Additional research including users from other demographic groups, such as other age groups, is required to generalize our findings and to increase external validity. Originality/value: Unique implications related to the role of user's achieved belongingness and perceived enjoyment of others in graphic-based emoticon usage in purchase intentions are found. Peer review: The peer review history for this article is available at: https://publons.com/publon/ 10.1108/OIR-02-2020-0036.
Keywords: Demographic groups; Design/methodology/approach; Empirical research; External validities; Perceived enjoyment; Perceived usefulness; Purchase intention; Structural modeling; Achieved belongingness; Emoticon purchase intention; Emoticon usage motives; Mobile instant messenger